Environmental properties of the southern Gulf of Aqaba, Red Sea, Egypt - DORGHAM, M.M.; EL-SHERBINY, M.M.; HANAFI, M.H. (Mediterranean Marine Science, 2012)
Environmental properties (temperature, dissolved oxygen, nutrients and chlorophyll a) of the epipelagic zone off Sharm El-Sheikh, Red Sea, Egypt were studied seasonally throughout a year from March 1995 to March 1996. Water samples were collected from five water depths (0, 25, 50, 75 & 100 m). The studied parameters exhibited clear seasonal variability along the water column. The vertical distribution of water temperature showed thermal homogeneity during most seasons, and thermal stratification in summer. Dissolved oxygen attained slightly high concentrations (5.3-7.8 mg l-1) in the whole water column, with slight seasonal variation. The concentrations of nutrients reflected dominant oligotrophic conditions in the epipelagic zone and occasional mesotrophic status at some depths. Phosphate fluctuated between 0-0.7 μM, ammonium (0-2.27 μM), nitrite (0-0.72 μM), nitrate (0-1.49 μM) and silicate (0-6.48 M). Phytoplankton biomass was generally low in the epipelagic zone throughout the study, whereas chlorophyll a was less than 0.5 μg l-1, except relatively high concentration (0.7-1.12 μg l-1) in deep layers in spring. In comparison with previous studies on the Gulf of Aqaba all environmental parameters during present study showed pronouncedly different values.